Analisis Implementasi Kurikulum Merdeka pada Mata Pelajaran Fiqih dalam Meningkatkan Pemahaman Peserta Didik: Studi Literatur - Alya Nur Affifah; Bagas Agamy Bakti; Firza Alkhairi; Miftahul Jannah; Nurul Zaman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in Fiqh subjects and how its application affects the improvement of students' understanding. Using the library research method, this study reviews various recent literature in the form of scientific articles, accredited journals, academic books, and relevant policy documents. The results of the study show that the Merdeka Curriculum is conceptually aligned with the principles of Islamic education, especially in terms of character development, freedom of learning, and student-centered learning. However, the implementation of this curriculum in Fiqh learning still faces a number of challenges, such as teachers' limited understanding of the new curriculum approach, a lack of project-based contextual teaching materials, and difficulties in conducting authentic assessments on aspects of worship and morals. Technical challenges such as the availability of facilities and access to technology also hamper the effectiveness of learning. This study emphasizes the need for continuous teacher training, the development of open-access learning resources, and improved infrastructure support in order to strengthen the implementation of the Merdeka Curriculum. Overall, this curriculum has significant potential to improve students' understanding of Fiqh if it is supported by appropriate and collaborative implementation strategies.